2021
DOI: 10.3389/fmolb.2021.622219
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics of Tumor Heterogeneity in Longitudinal Dynamic Contrast-Enhanced Magnetic Resonance Imaging for Predicting Response to Neoadjuvant Chemotherapy in Breast Cancer

Abstract: Breast tumor morphological and vascular characteristics can be changed during neoadjuvant chemotherapy (NACT). The early changes in tumor heterogeneity can be quantitatively modeled by longitudinal dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI), which is useful in predicting responses to NACT in breast cancer. In this retrospective analysis, 114 female patients with unilateral unifocal primary breast cancer who received NACT were included in a development (n = 61) dataset and a testing dataset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 38 publications
0
37
0
Order By: Relevance
“…Most of the previous research on breast cancer radiomics only focused on the features extracted from one single phase after enhancement [25,26]. The prediction performance of other phases of DCE-MRI was still relatively unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the previous research on breast cancer radiomics only focused on the features extracted from one single phase after enhancement [25,26]. The prediction performance of other phases of DCE-MRI was still relatively unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the molecular-only LDA and MLP model achieved an AUROC of 0.744 and 0.752 in the breast cancer patients, higher than kinetic-only and image-only predictive models. However, the molecular information is acquired via invasive needle biopsy, which cannot reflect certain pathophysiological characteristics of tumors, such as microvascular density and permeability, and tumor heterogeneity, which is known to be relevant to the sensitivity of pCR NAC in breast cancer ( 15 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…RA relies on a pipeline including extraction of numerous handcrafted imaging features, followed by feature selection and then machine learning-based classification ( 11 ). However, the performance of radiomics models derived from pretreatment DCE-MRI is limited in predicting pCR with an AUROC ranging from 0.568 to 0.79 ( 12 , 15 , 16 ). DL can automatically learn discriminative features directly from images without the necessity of feature predefinition ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Radiomics is a rapid developing field of medical study that quantitates the microstructure and biological information of tumor tissue for exploring the intra-tumoral heterogeneity and tumor characterization in a convenient and non-invasive way ( 22 ). To date, some studies have already investigated the discrimination between benign and malignant breast tumors ( 23 , 24 ), lymph node metastasis ( 25 27 ), tumor response prediction of neoadjuvant chemotherapy ( 28 , 29 ), and survival analysis ( 30 , 31 ). Our study found that radiomics showed favorable predictive performance on molecular subtype based on the DCE-MRI images.…”
Section: Discussionmentioning
confidence: 99%